Latrine Utilization and its Associated Factors in Urban Slums Dwellers of Gondar City, Northwest Ethiopia: A Community-Based Cross-Sectional Study - Getasew Yirdaw; Awrajaw Dessie; Jember Azanaw; Tsegaye Adane Birhan (Environmental Health Insights, 2023)
Background: Sanitation facilities are critical for interrupting the transmission of feco-oral disease through proper use, not simply their physical presence. Latrine utilization is the actual behavior in a practice of regularly using existing latrines for the safe disposal of excreta. In slum regions of developing nations, such as Ethiopia, poor latrine use is a prevalent concern. As a result, the purpose of this study was to examine the state of latrine utilization and its determinant factors in the urban slums of Gondar City, Northwest Ethiopia. Methods: A cross-sectional survey was done in slum regions of Gondar City from March 1 to April 30, 2021, with a total of 422 systematically chosen households. A structured pre-tested questionnaire and on-the-spot observational checklists were used to collect the data from each household. Result: Latrine utilization was observed among 31.5% of households. Latrine utilization was also significantly associated with the age of the latrine (age ⩽10 years) (AOR: 2.31; 95% CI (1.15, 4.63)), cleanliness of the latrine (AOR: 3.70; 95% CI (1.16, 11.78)), pit being lined (AOR: 6.33; 95% CI (2.09, 19.15)), depth of latrine (⩽3 m) (AOR: 0.43; 95% CI (0.24, 0.77)), and cleaning materials for handwashing (AOR: 0.33; 95% CI (0.15, 0.75)). Conclusion: Based on the present finding, most households didn’t have proper latrine utilization practices. The age of the latrine, cleanliness of the latrine, pit being lined, depth of the pit, and cleaning materials for handwashing were associated factors of latrine utilization. As a result, sanitation interventions such as health education about improving the cleanliness and sanitary condition of existing latrine facilities and constructing lined and deep new latrines as the goal’s standard should be implemented.